Analysis Of Code Mixing And Code Switching In Teaching-Learning Process In Kelas Internasional-Net Tv - I Gede Neil Prajamukti Wardhana; Gina Ivana Membrasar; Ni Luh Desy Suari Dewi; Gek Wulan Novi Utami (International Journal of Linguistics and Discourse Analytics, 2023)
The aim of the research is to find out kinds of code switching and code mixing, the dominant one in teaching and learning process in a television program by Kelas International on Net TV. The data was analyzed by using Hoffman theory of code switching and code mixing (1991) and the data of this research was taken from the learning process in Kelas International focused in episode 97 part one and two and the average duration of each part is 6-10 minutes. This research was conducted by using Descriptive Qualitative Research. Based on the data analyzed, it turns out that there were four types of code switching found in Kelas International namely Intra sentential Switching, inter sentential switching, emblematic switching and Maintaining Continuity with The Prior Speaker. Beside that also found that there are three types of code mixing namely Intra sentential, Intra Lexical and Involving Change Pronunciation. The most dominant type of code switching is Emblematic type used six times in code switching, while change pronunciation type used four times in code mixing, is the type that is most frequently used. This research purposes is to understanding language codes utilized in communication that frequently occur and are employed in the teaching and learning process